Contractor And Visitor Management System Using Biometric Recognition (Vizika System) - Nur Alia Hidayah, Rohaya Udin (2023)
This project was built to help organizations in KANEKA Malaysia to track visitors entering and exiting their premises. These systems typically include a registration process, where visitors provide their personal and contact information, as well as a check-in process. Visitor Management Systems also include features such as appointment scheduling, automatic notifications and analytics to help organizations improve the visitor experience and manage their facilities more efficiently. Overall, a Visitor Management System is a tool that aims to streamline the check-in process for visitors, improve security and provide valuable insights for organizations.